Pengaruh Model Pembelajaran PBL Berbasis Outdoor Study pada Materi Pencemaran Lingkungan terhadap Keterampilan Berpikir Kritis dan Motivasi Belajar di SMA Pembina Palembang - Salsabilla, Alfidda; Anggraini, Nike; Nazipetc, Khoiron (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to examine the effect of applying the Problem Based Learning (PBL) model with an Outdoor Study strategy on environmental pollution material toward students’ critical thinking skills and learning motivation in Grade X at SMA Pembina Palembang. The research employed a quasi-experimental method with a non-equivalent control group design. The population consisted of two classes, namely class X1 (29 students) as the experimental group and class X2 (19 students) as the control group. Data were collected through interviews, classroom observations, critical thinking skill tests, and learning motivation questionnaires. Based on the findings, the hypothesis test using the Independent Samples Test showed a significance value of 0.000 (<0.05), indicating a significant effect of PBL with Outdoor Study on students’ critical thinking skills. The experimental class achieved an average final score of 77 with a 55% improvement (N-gain), which was higher than the control class with an average score of 58 and a 27% improvement. Regarding learning motivation, the Mann Whitney-U test also showed a significance value of 0.000 (<0.05), indicating a significant effect on increasing motivation. The experimental class reached an average score of 94 with a 73% improvement (N-gain), while the control class scored an average of 86 with an 11% improvement. In conclusion, the implementation of the PBL model with an Outdoor Study strategy has a positive and significant impact on enhancing students’ critical thinking skills and learning motivation in environmental pollution material at SMA Pembina Palembang.